2019
DOI: 10.1016/j.jbankfin.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Operational risk and reputation in financial institutions: Does media tone make a difference?

Abstract: Operational risk announcements are unexpected adverse media news that potentially harm the reputation of financial institutions. This paper examines the equity-based and debt-based reputational effects of financial sentiment tones in operational risk announcements and shows how such reputational effects are moderated by alternative sources of public information. Our analysis reveals that the net negative tone and litigious tone have adverse reputational effects, and the uncertainty tone mitigates the adverse r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 56 publications
1
30
0
2
Order By: Relevance
“…Particularly, this study uses the participation degree (PD) to express the probability of social media participating in the regulatory process. Its exposure to security risks will harm the reputations of companies and cause a loss for them [58]. This study also uses impact power (IP) to indicate the extent and coverage of security issues reported in social media.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Particularly, this study uses the participation degree (PD) to express the probability of social media participating in the regulatory process. Its exposure to security risks will harm the reputations of companies and cause a loss for them [58]. This study also uses impact power (IP) to indicate the extent and coverage of security issues reported in social media.…”
Section: Model Descriptionmentioning
confidence: 99%
“…in measurement modeling (Eckert & Gatzert, 2015). Barakat et al (2019) concluded that the loss of reputation is higher in cases where the media uses negative and strong language when announcing the OR losses. Therefore, it is emphasized that even the attitude toward risk of employees who are communicating with the public has importance.…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%
“…These potential risks are true for all sectors of industry operating in the social media space. However, it could be argued that the financial sector, including those operating in South Africa, carries a higher prospect of possible damage to reputation and loss of revenue given the sensitivity in managing financial resources, and the volatility attached to operational losses that have seen a number of financial disturbances including the collapse of some institutions over the last two decades (Barakat et al, 2019;Ferreira et al, 2019). Raj and Sindhu (2013) highlight that it is imperative that those within the finance system identify and measure various risks faced and initiate suitable remedies to mitigate them.…”
Section: Social Media Policiesmentioning
confidence: 99%
“…For Raj and Sindhu (2013), Demek et al (2018) as well as Barakat et al (2019), there are key identifiable characteristics, which make researching the financial sector advisable, as follows: Client trust is paramount to sustainability and success. Therefore, organizations in the financial sector need to adopt clear management strategies to manage social media to avoid potential risks to the organization (Benthaus et al, 2016).…”
Section: Social Media Policiesmentioning
confidence: 99%